(3hQO GdhQhO hajV GdHMQ GdehQhOs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s ((3YeQ Hf YKeGf GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg TGQM eYGfi GdUOhQ CeG HYO ajbhd (B: (3YHO GdZfi GHf GdfGHdSi hQO YdjfG hGQO ef HYV GdeMHjf ai HdGO GdQhe HTQM GdUdhGJ GdeMeOjI GdefShHI Edi eMji GdOjf eMeO Hf Ydi GdMGJei GdCfOdSi s
(3BNQgG (B:s
(3WQJ (B: (3gi ai GdCUd caI GdKhH hGdLeY WQQ eKd ZQI hZQQ , PcQg ai GdeUHGM hbGd ai s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
Keywords: (3GdJUha hGdBOGH GdTQYjIs